Percepción del apoyo social y calidad de vida en pacientes oncológicos con tuberculosis que acuden a consultorios externos inen - Cordova-Santiago, Liz-Gelin (2022)
Objective: To determine the perception of social support and quality of life in cancer patients with tuberculosis attending outpatient clinics of the national institute of neoplastic diseases in 2021. Methodology: The study had a quantitative, correlational, cross-sectional, non-experimental design. The population consisted of approximately 80 oncology patients with tuberculosis attending the INEN tuberculosis prevention and control program. Two instruments were used; the MOS questionnaire of Social Support in Primary Care (De la Revilla et al., 2005), to measure social support with 4 dimensions: Emotional, positive social interaction, instrumental and affective with 14 items and the WHOQOL-BREF quality of life scale, which evaluates 4 dimensions: physical health, psychological health, social relationships and environment, with 26 items both instruments with a Likert scale that were validated by expert judgment and a pilot test was performed to obtain Cronbach's alpha. The results obtained were that there is a Spearman correlation indicating that there is a moderate relationship between perception social support and the quality of life in oncology patients with tuberculosis (Rho= ,582), which means that both variables are significant (p= ,000 < ,05).